2020
DOI: 10.1186/s40101-020-00232-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin receptor gene polymorphism (rs53576) and digit ratio associates with aggression: comparison in seven ethnic groups

Abstract: Background The specific role of the oxytocin receptor ( OXTR ) gene polymorphisms in emotional support seeking, related to social norms and culturally normative behavior, has been discussed in several studies. Evidence on the association between aggression and OXTR polymorphisms has also been reported. The goal of the current study was to analyze the effect of the OXTR rs53576 polymorphism, prenatal testosterone effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 129 publications
2
12
0
Order By: Relevance
“…These findings indicated that physical aggression may be associated with hostility. In addition, the higher anger scores in females than in males were also similar to the results in Isanzu and Buryats (Butovskaya et al, 2020). Additionally, an fMRI experiment of facial expressions also showed higher anger recognition levels in females than in males (Dores, Barbosa, Queiros, Carvalho, & Griffiths, 2020), which indicates their emotional dysregulation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings indicated that physical aggression may be associated with hostility. In addition, the higher anger scores in females than in males were also similar to the results in Isanzu and Buryats (Butovskaya et al, 2020). Additionally, an fMRI experiment of facial expressions also showed higher anger recognition levels in females than in males (Dores, Barbosa, Queiros, Carvalho, & Griffiths, 2020), which indicates their emotional dysregulation.…”
Section: Discussionsupporting
confidence: 85%
“…First, our study only included Chinese samples to avoid stratification artifacts. Previous studies have shown that cultural background may influence aggression behavior (Butovskaya et al, 2020; Hyde, 2014; Ramirez et al, 2001). Therefore, further studies in different populations are needed to clarify the effect of sex on aggression in different populations.…”
Section: Discussionmentioning
confidence: 98%
“…Although a unique consensus is still not reached and may depend on the alleles’ distributions within a specific sample, the A allele is usually combined with the same heterozygous group A/G in the Western samples, whereas the G allele is more commonly paired with the heterozygous group A/G in the Eastern samples [29,35,44,45]. In cross-cultural investigations analyzing different ethnic groups as a whole, reducing the number of genetic groups, A/A is maintained in contrast with the combined couples A/G and G/G [38,46].…”
Section: Methodsmentioning
confidence: 99%
“…In Russia, the statistics mirror international trends in time pre-pandemic, with males reported utilizing physical aggression scores significantly higher than females, while females slightly exceeding males in using verbal aggression, anger, and hostility up, with a mean between 12 and 24% ( 5 , 6 ). These differences in aggression behavior are similar in both school children as well as adult Russians ( 7 ).…”
Section: Introductionmentioning
confidence: 85%